Microstructural characterisation and electrical properties of multiwalled carbon nanotubes/glass-ceramic nanocomposites - Giovanardi, Roberto; Montorsi, Monia; Ori, Guido; Cho, Johann; Subhani, Tayyab; Boccaccini, Aldo R.; Siligardi, Cristina (Journal of Materials Chemistry, 2010)
We report on an improved processing method for fabricating multiwalled carbon nanotubes/glass-ceramic nanocomposites based on vanadium doped silicate glass matrices. Starting from the design of a stable aqueous dispersion of CNTs, achieved using a cationic surfactant, the interaction of CNTs with glass particles in suspension was improved using a co-solvent that provided access to nanocomposites exhibiting high quality CNT distribution in the matrix, which was confirmed by detailed micro/nano-structural and morphological characterisation. Considering that very few studies have focused on the functional properties of CNT/glass composites, in the present investigation the electrical resistivity of CNT/glass composites was measured and it was demonstrated that higher electrical conductivity values were obtained compared to previous similar materials fabricated by conventional powder processing. © 2010 The Royal Society of Chemistry.
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.micros